2008
DOI: 10.1097/pai.0b013e31806d9b88
|View full text |Cite
|
Sign up to set email alerts
|

Mean Nuclear Area and Metallothionein Expression in Ductal Breast Tumors: Correlation With Estrogen Receptor Status

Abstract: Breast carcinoma is the most common malignancy in women. Estrogen is an important growth factor for breast tumor that plays an important role in regulating the proliferation and differentiation of normal and malignant mammary epithelial cells. Nuclear morphometry and metallothioneins (MTs) are indicators of proliferation that have been used as predictors of prognosis in many tumors. The present study aimed to study mean nuclear area (MNA) and MT; estrogen receptor (ER) expression in fibroadenoma (FA), ductal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
9
0
3
Order By: Relevance
“…Compared to non-malignant tissues, significantly higher MT staining was identified in gallbladder cancer [91], a significant decrease in colorectal [92] and cervical [93] tumors and no associations were observed in ductal breast tumors [94] and glioblastomas [95]. Immunohistochemical-based studies of other tumors were not identified.…”
Section: Resultsmentioning
confidence: 86%
“…Compared to non-malignant tissues, significantly higher MT staining was identified in gallbladder cancer [91], a significant decrease in colorectal [92] and cervical [93] tumors and no associations were observed in ductal breast tumors [94] and glioblastomas [95]. Immunohistochemical-based studies of other tumors were not identified.…”
Section: Resultsmentioning
confidence: 86%
“…In Ref. [6], automatic measurements of mean nuclear area in breast cancer cells were performed using an advanced image processing and analysis system. Similarly in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, breast tumor MT overexpression is associated with a poorer prognosis (Jin et al 2004). A remarkably clear correlation exists in breast tumors between MT overexpression and poor ER expression (El Sharkawy and Farrag 2008), indicating that increased MT may be another basal-like phenotype marker. Tissues often accumulate cadmium associated with MT (Cherian et al 2003).…”
Section: Discussionmentioning
confidence: 99%